ASSOCIATION OF SERUM LACTATE DEHYDROGENASE AND GAMMA-GLUTAMYL TRANSFERASE WITH PRE-ECLAMPSIA - KUMARI, NEETU; SUTHAR, NEHA; KAUR, JASWANT; DWIVEDI, JYOTI; K, VYAS R (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Pre-eclampsia produces potentially lethal complications including placental abruption, hepatic failure, acute renal failure, and cardiovascular collapse. The present study was planned to find the association between serum lactate dehydrogenase (LDH) and gamma-glutamyl transferase (GGT) with pre-eclampsia and compare it with normal healthy control. Methods: This hospital-based case–control study was conducted in the biochemistry department in collaboration with the Department of Gynaecology, Sardar Patel Medical College, Bikaner (Raj). 50 subjects to find whether there are any changes in the levels of serum LDH and GGT in pre-eclamptic patients (case group) compared to that of 50 normal pregnant women (control group). Results: The present study has shown statistically significant (p<0.001) increases in serum LDH levels and GGT in pre-eclamptic patients compared to control subjects. Conclusion: Serum LDH and GGT screening in early pregnancy may be helpful in predicting the occurrence of pre-eclampsia.